The Influence of Vanadium Source and Calcination Temperature on Na3V2(PO4)3 Cathode Material - Weijian SONG; Ping LI; Zhuangzhi LI; Jiahui ZHAO; Xiaobin NIU; Xiaoxia DUAN; Zhenguo WU (Shiyou huagong gaodeng xuexiao xuebao, 2025)
Sodium vanadium phosphate (Na3V2(PO4)3, abbreviated as NVP）, exhibits unique advantages in sodium⁃ion batteries due to its excellent thermal stability and broad sodium⁃ion transport channels. However, the expensive vanadium raw materials have diminished the attention on the commercial development of NVP. In this work, NVP was successfully synthesized using solid⁃state methods from NaVO3, a byproduct from the upstream of the vanadium extraction industry, and compared with NVP synthesized from V2O5 and NH4VO3 at different calcination temperatures. The results indicate that the vanadium source has a significant impact on the structure and morphology of NVP, which further influences the battery capacity and rate performance. NVP prepared using NaVO3 at 750 ℃ exhibits excellent electrochemical performance, achieving an initial high capacity of 105.6 mA·h/g at 0.1 C, and still obtaining high capacities of 101.5, 99.9, and 92.9 mA·h/g at subsequent rates of 1.0, 2.0, and 5.0 C, respectively. Moreover, it achieves a reversible capacity of 97.1 mA·h/g and a high capacity retention rate of 94.6% after 300 cycles at 1.0 C, and retains 94.0% capacity after 500 cycles at 5.0 C. This simple, efficient, and cost⁃effective synthesis strategy provides a reference for the scaled⁃up production of NVP.